KERAGAMAN MORFOLOGI MODIFIKASI BATANG (CAULIS) DI KECAMATAN LUBUKLINGGAU TIMUR I, LUBUKLINGGAU - Reny Dwi Riastuti; Nopa Nopiyanti; Yuli Febrianti (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this research that has been carried out is to analyze the diversity of morphology of stem modification (caulis) in the Sub-District of East Lubuklinggau I. The technique of collecting the data that has been carried out by observation. The data obtained from the study were analyzed descriptively qualitatively and quantitatively. The results of the study have found 29 species, namely 12 species that have cirrhus, namely Pisum sativum, Psophocarpus tetragonolobus, Vigna sinensis, Ipomoea batatas, Piper betle, Cucumis sativus, Momordica charantia, Cucurbita moschata, Passiflora quadrangularis, Cylea barbata, Vitis vinifera, Mikania micrantha, 7 species that have rhizomes, namely Cyperus rotundus, Etlingera hemisphaerica, Alpinia galangal, Kaempferia galangal, Zingiber officinale, Zingiber cassumunar, and Curcuma domestica, 4 species that have geragih, namely Cyperus rotundus, Marsilea crenata, Fragaria vesca and Solanum tuberosum , 4 species that have tuber namely Ipomoea batatas, Colocasia esculenta, Cyperus rotundus, and Solanum tuberosum, 3 species that spina, namely Solanum torvum, Hylocereus costaricensis, and Mammillaria xanaea, 1 species that has a bulb namely Amaryllis fariegata temporal sangat tinggi (Servina and 1 species that has tuber namely Musa paradisiaca, and diversity index (H') is 1.284 categorized as medium diversity.